Minimal excess risk of cancer and reduced risk of death from cancer in Australian Department of Veterans' Affairs clients: a record linkage study. (4th February 2014) - Vajdic, Claire M.; Stavrou, Efty P.; Ward, Robyn L.; Falster, Michael O.; Pearson, Sallie‐Anne
Abstract Objective: To quantify the risk of incident cancer and cancer‐related mortality in Australian Government Department of Veterans' Affairs (DVA) clients. Methods: A population‐based record linkage study of 75, 482 adult clients residing in New South Wales (NSW) from 2000 to 2007; median age 75 years (interquartile range, 68–79); 57% male. Standardised incidence ratios (SIRs) and mortality ratios (SMRs) for any cancer and by cancer type were calculated, relative to the NSW population. Results: The risk of any cancer was slightly increased for males (SIR 1.07, 95%CI 1.04–1.10) but not females (SIR 1.00, 95%CI 0.96–1.04). Males exhibited a significantly elevated risk of prostate cancer (SIR 1.08), cutaneous melanoma (SIR 1.19), head and neck cancer (SIR 1.27) and connective tissue cancer (SIR 1.52). Females did not exhibit excess risk for any cancer type. Risk of cancer death was significantly reduced for any cancer (male SMR 0.78, 95%CI 0.75–0.81; female SMR 0.80, 95%CI 0.76–0.85) and for a range of haematopoietic and solid neoplasms including prostate (SMR 0.57), breast (SMR 0.62) and colon cancer (male SMR 0.67; female SMR 0.71). Conclusion: Cancer incidence rates are largely similar, and mortality rates moderately lower, for DVA clients compared to the NSW general population. Implications: These risk patterns may reflect service‐related history, a healthy‐survivor effect, competing risk of death, and/or comprehensive health care entitlements with minimal to no co‐payments. Our findings suggest DVA clients are probably accessing cancer screening services. Outcomes after cancer diagnosis are good, most probably due to comprehensive health care entitlements.